PELAJARAN MENULIS ESAI DARI ESAI-ESAI SOSIAL BUDAYA ARIEF BUDIMAN - S, Sudibyo (Hiski Malang, 2024)
This article aims at discussing how to write essay from the reading of Arief Budiman’s sociological essays. An essayist is different from a critic. A critic is essentially an observer or a researcher. Their goal is to achieve a fundamental understanding of a specific literary work they are examining and to prove their understanding by providing explanations of the elements that constitute it, in order to assess whether the work in question is successful or failed. In contrast, an essayist is essentially a thinker. The tangible results of a critic's and an essayist's work can be understood, for example, from a piece that analyzes a collection of poems by a poet compiled in *Di Bawah Kibaran Sarung* by Joko Pinurbo. From the analysis, the writer discovers something new in the poems of this collection, namely a phenomenon that intensely explores body symbolism, offering new movement. Whereas poets usually seek symbolism from the body to nature, this movement shifts to finding symbolism from nature brought back to the body. For the writer, this phenomenon leads to reflections on the body as an indicator that provides information about many aspects of society and culture.